IPTU e extrafiscalidade - Souza, Vanderson Silva de (2022)
This is the extra-fiscal function of the tax rule of the urban land and territorial property tax, especially with regard to its admissibility by the Brazilian legal system, its manifestations and form of control. To this end, we discuss: the tax jurisdiction of municipalities and its importance; the constitutional principles of tax legality, the ability to pay, the prohibition of the tax confiscatory effect; and extrafiscality, registering some doctrinal concepts, criteria to identify the norm with extrafiscal function and its correlation with the aforementioned constitutional principles. From the above, it is shown that the national legal system authorizes the application of extrafiscality to the tax on urban land and land property, not only because there is an express constitutional provision of progressive rates to meet the social function of property, but also because, pursuant to the authorization provided for in article 156, §1, item II, of the Federal Constitution, it is possible to adopt differentiated rates based on the use and location of the property, provided that it is aimed at some constitutionally foreseen purpose, being important to carry out control of the norm with the function of extrafiscal This reasoning also applies to extra-fiscal exemptions